Affine Locally Symmetric Surfaces in $\boldsymbol{R}^4$ (Communications in Mathematical Research, 2021)
The nondegenerate affine locally symmetric surfaces in $\boldsymbol{R}^4$ with thetransversal bundle defined by Nomizu and Vrancken$^{[1]}$ have been studied and a complete classification of the locally symmetric surfaces with flat normal bundle has beengiven.
Keywords: locally symmetric surface; flat normal bundle; equiaffine normal bundle.